1990
DOI: 10.1017/s1446788700035680
|View full text |Cite
|
Sign up to set email alerts
|

Monomial representations and generalizations

Abstract: We study the characteristic p analogue of M-groups, the so-called M p -group Generalizing this notion, we also consider the condition that the modular irreducible representations are induced from representations of dimension < p, or even weaker, of dimension not divisible by p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For example, ) 3 , 2 ( SL is an 2 M -group but not an M -group. In [4], Bessenrodt confirmed that p M -groups are solvable. In [5] Hanaki and Hida investigated conditions for p M -groups to be M -groups and proved that if G is p -nilpotent then G is an M -group if and only if G is an p M -group.…”
Section: Introductionmentioning
confidence: 93%
“…For example, ) 3 , 2 ( SL is an 2 M -group but not an M -group. In [4], Bessenrodt confirmed that p M -groups are solvable. In [5] Hanaki and Hida investigated conditions for p M -groups to be M -groups and proved that if G is p -nilpotent then G is an M -group if and only if G is an p M -group.…”
Section: Introductionmentioning
confidence: 93%